Patient preferences for the integration of mental health counseling and chronic disease care in South Africa - Myers-Franchi, Bronwyn; Joska, J.A.; Lund, C.; Levitt, N.S.; Butler, C.C.; Naledi, T.; Milligan, P.; Stein, D.J.; Sorsdahl, K. (DOVE MEDICAL PRESS LTD, 2018)
Purpose: To describe patient perceptions of the acceptability of integrating mental health counseling within primary care facilities in the Western Cape province of South Africa and their preferences for the way in which this care is delivered.